Ge/NiGe bilayer applied for the recording film of write-once blu-ray disc. (August 2015) - Ou, Sin-Liang; Chen, Sheng-Chi; Lin, Yan-Cheng; Kuo, Tsung-Yen; Wen, Chao-Kuang
Abstract: In this study, the Ge/NiGe (3 nm/16 nm) bilayer was deposited by sputtering at room temperature to serve as the recording film for write-once blu-ray disc. The thermal properties, optical characteristics, crystallization mechanisms and recording performance were all investigated in detail. The composition of the NiGe alloy layer was maintained at Ni50 Ge50 . Based on the results of reflectivity-temperature measurements, it can be observed that the Ge/NiGe bilayer had two temperature ranges of reflectivity increment, i.e. 170–216 °C and 340–352 °C. Microstructural analysis revealed that the NiGe nano-crystalline phase was generated in the as-deposited state. After annealing at 250 °C, the crystallinity of the NiGe phase was improved. Upon further increasing the annealing temperature to 370 °C, the Ge crystallization appeared in this bilayer. Dynamic tests indicate that the blu-ray disc fabricated with the Ge/NiGe recording layer possesses optimum jitter values of 6.4% and 7.1% at 1× and 4× writing speeds, respectively. This implies that the Ge/NiGe bilayer has high potential for write-once blue laser recording applications. Highlights: Ge/NiGe bilayer was prepared as recording film of write-once blu-ray disc. Crystallization temperature of Ge was reduced significantly using Ge/NiGe film. Optimum jitter value of Ge/NiGe blu-ray disc is 7.1% for 4× recording speed.